Paleobotany plants of the past, their evolution, paleoenvironment, and application in exploration of fossil fuels - Agashe, Shripad N. (Enfield, N.H Science Publishers, 1997)
Text book in paleobotany with special reference to India.
Includes bibliographical references (p. [316]-342) and index.
Keywords: Paleobotany; Plants, Fossil -- India